The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4236/msa.2011.211210
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Power of Cu-Zn Ferrites

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Moreover, Seebeck coefficient increases with increasing temperature up to a certain temperature T S , beyond which, the value of S becomes constant or starts to decrease. Many researchers [4,5,7,19], attributed this transition temperature to a magnetic transition from ferrimagnetic to paramagnetic state, which contradicts with our results. Kale et al [9] studied the cation distribution for Ni 1 þ x Ti x Fe 2 À 2x O 4 and reported that Ni 2 þ occupies octahedral B-sites, whereas both Fe 3 þ and Ti 4 þ ions are distributed over tetrahedral (A) and octahedral (B) sites.…”
Section: Resistivitycontrasting
confidence: 85%
See 1 more Smart Citation
“…Moreover, Seebeck coefficient increases with increasing temperature up to a certain temperature T S , beyond which, the value of S becomes constant or starts to decrease. Many researchers [4,5,7,19], attributed this transition temperature to a magnetic transition from ferrimagnetic to paramagnetic state, which contradicts with our results. Kale et al [9] studied the cation distribution for Ni 1 þ x Ti x Fe 2 À 2x O 4 and reported that Ni 2 þ occupies octahedral B-sites, whereas both Fe 3 þ and Ti 4 þ ions are distributed over tetrahedral (A) and octahedral (B) sites.…”
Section: Resistivitycontrasting
confidence: 85%
“…Among spinel ferrites, pure nickel ferrite NiFe 2 O 4 , is particularly important during the last few decades. Studies of Ni-ferrites with different metal ions such as Cu, Zn, Cd, Li, Co and Mg have been carried out by many workers [3][4][5][6][7][8]. Kale et al studied the crystal structure and Mössbauer spectra for Ti 4 þ substituted nickel ferrite and established a detailed map for cation distribution in Ti x Ni (1 þ x) Fe (2 À 2x) O 4 ferrite [9].…”
Section: Introductionmentioning
confidence: 98%
“…for example LI Zi-heng [1], discover the properties can be used as cell voltage [10] and as photo catalys activity [6]. In 1997 veingangkar found Cu 0.8 Zn 0.2 Fe 2 O 4 properties that are able to absorb water from the air (hygroscopic) [11]. D Revinder, 2000, found as a thermoelectric properties were obtained at Ferrite with Cu and Zn atoms.…”
Section: Introductionmentioning
confidence: 99%